Development and Testing of Metacognitive Therapy for Prolonged Grief Disorder: A Randomised Controlled Trial - Wenn, Jenine Anne (Curtin University, 2017)
This study investigated the metacognitive processes involved in Prolonged Grief Disorder, and developed and tested a group Metacognitive Grief Therapy for people experiencing prolonged grief symptomatology. Feasibility, efficacy and acceptability of the Metacognitive Grief Therapy program was tested in a pilot randomised controlled trial, with a 3- and 6-month follow-up. The findings supported the utility of Metacognitive Grief Therapy for reducing psychological distress and improving quality of life for people experiencing prolonged grief symptomatology.